(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article discusses the importance of a healthy lifestyle and maintaining human health. The author analyzes a healthy lifestyle as the main guarantee of a quality life, studies the formation of a healthy lifestyle and the level of their health among volunteer students. It also indicates to what extent students follow a healthy lifestyle and what diseases and problems they encounter while maintaining a healthy lifestyle. A healthy lifestyle is the basis for maintaining physical and mental well-being. It includes a series of habits and practices that help strengthen the body, maintain energy and improve quality of life. In the research article below, we’ll look at the key aspects of a healthy lifestyle and how to implement them into your daily life.